我的麻吉實習輔導老師：實習輔導教師教學風格與實習教師學習風格關係之研究 Mentor Match - A Study on the Relationship between the Teaching Style of Practicum Mentor and the Learning Style of Student-Teacher - 黃泓霖 Huang, Hong-Lin; 劉唯玉 Liu, Wei-Yu (National Changhua University of Education, 2013)
本研究以Grasha 之教學風格與Silver 與Hanson 之學習風格觀點，立意取樣四組教學與學習風格明顯，且為不同配對組合者為研究對象。以訪談法為主，觀察法為輔，試圖瞭解師徒式教育實習中實習輔導老師教學風格與實習教師學習風格之交互關係及其對師徒關係與實習結果的影響。研究發現，麻吉組合為授權型vs.自我表達型，以及促進型vs.注重人際型。不麻吉組合為授權型vs.注重人際型。研究發現麻吉組之實習教師滿意實習輔導教師之指導方式；實習教師的學習動機與學習表現佳；實習輔導教師滿意實習教師之學習行為與表現，肯定個人指導方式並持續提供指導；師徒關係良好發展順利。不麻吉組之實習教師無法獲得所需之指導方式，師徒關係發展不順利，也影響到實習教師之實習過程與實習結果。 Based on Grasha's teaching style and Silver and Hanson's learning style perspectives, this study aims to understand and explore the interactions between mentor's teaching style and student-teacher's learning styles and their influences on the relationships between mentors and student-teachers and student-teachers' internship learning results. The researchers purposefully sampled four different combinations of practicum mentor and student-teacher for interviews and observations. The result shows that the delegator/self-expressive combination, and the facilitator/interpersonal combination lead to a satisfactory practicum. However, the delegator/interpersonal combination produces poor results, even problems, in terms of all three aspects, namely practicum progress, mentorship, and practicum outcome.